Engineering problem solving : a classical perspective - Shaw, Milton C. (Milton Clayton), 1915-2006 (Materials science and process technology series. Electronic materials and process technology., 2001)
" ... revisits the development of engineering as a problem-solving profession, beginning from its origins in the classic text: Dialogues Concerning Two New Sciences, by Galileo Galilei, originally published in 1638 ... discussions of passages from the Galileo text emphasize the roles played by experimentation and dialog in engineering analysis and creativity; that is, the 'mind' set of engineering. Throughout this book, the often-circuitous route taken in the development of new ideas is illustrated"--Page 4 of cover.